Межові версії теореми Ворпіцького для двовимірних неперервних дробів - Кучмінська, Х.Й. (Український математичний журнал, 2014)
Для двумерной непрерывной дроби доказано еще одно обобщение теоремы Ворпицкого и предложены граничные множества в теоремах типа Ворпицкого, когда множества элементов двумерной непрерывной дроби заменены их границами. For a two-dimensional continued fraction another generalization of the Worpitzky theorem is proved and the limit sets are proposed for Worpitzky-like theorems in the case where the element sets of the twodimensional continued fraction are replaced by their boundaries.